Dialysate bicarbonate concentration: Too much of a good thing?. Issue 6 (8th June 2018) - Basile, Carlo; Rossi, Luigi; Lomonte, Carlo
Abstract: Acid‐base equilibrium is a complex and vital system whose regulation is impaired in chronic kidney disease (CKD). Metabolic acidosis is a common complication of CKD. It is typically due to the accumulation of sulfate, phosphorus, and organic anions. Metabolic acidosis is correlated with several adverse outcomes, such as morbidity, hospitalization and mortality. In patients undergoing hemodialysis, acid‐base homeostasis depends on many factors: net acid production, amount of alkali given by the dialysate bath, duration of interdialytic period, as well as residual diuresis, if any. Recent literature data suggest that the development of postdialysis metabolic alkalosis may contribute to adverse clinical outcomes. Unfortunately, no randomized studies exist about the effect of different dialysate bicarbonate concentrations on hard outcomes, such as mortality. Like everything else in dialysis, the quest for the "ideal" dialysate bicarbonate concentration is far from over. The Latin aphorism " ne quid nimis " ie "nothing in excess" (excess of neither acid nor base) probably best summarizes our current state of knowledge in this field. For the present, the clinician should understand that target values for predialysis serum bicarbonate concentrations have been established primarily based on observational studies and expert opinion. On the basis of this information, we should keep predialysis serum bicarbonate concentrations at least at 22 mEq/L. Furthermore, a specific focus should be addressed to the clinical and nutritional status of the major outliers on both the acid and alkaline sides of the curve.